PENGARUH EKSPOR-IMPOR, INFLASI, PENGANGGURAN TERHADAP GDP INDONESIA DAN AMERIKA SERIKAT - Faradilla, Allya Rahma; Setyowati, Eni; Hasmarini, Maulidyah Indira; Kuncoro, Trian Gigih (ITB AAS Indonesia Surakarta, 2024)
This research aims to analyze the influence of exports, imports, inflation and unemployment on Indonesian and American GDP for the 1997-2021 period. The method used in this research is multiple linear regression with the f test and t test. GDP, inflation and unemployment data are taken from the IMF, exports and imports are taken from the world bank. The results of this research show that the import variable has a significant positive influence on economic growth in the United States, but does not have a significant influence on economic growth in Indonesia. The inflation variable has a positive and significant influence on economic growth in Indonesia, but does not have a significant influence on economic growth in the United States. The unemployment variable has a negative and significant influence on economic growth in Indonesia, but does not have a significant influence on economic growth in the United States. The export variable has a positive but insignificant influence on economic growth in Indonesia and United States during 1997-2021.. Keywords : GDP, Pengangguran, Ekspor, Impor, Inflasi.